A history of intergroup relations in New Zealand : a trade-off between Māori agency and inclusion : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University, Albany, New Zealand - Choi, Yun-Seon (Sarah) (Massey University, 2019)
Growing fragmentation in historical attitudes can be observed alongside increasing political polarization and conflict in many societies, with both of these trends mutually reinforcing each other. Amidst these dynamics, there is a growing urgent need to understand both the politics and psychology of collective remembering. Although there has been much theorizing about the ways that historical narratives are curated by political elites and institutions in ways that promote a positive and moral image of the nation, there has been a lack of research investigating the ways in which such narratives are actually received, internalized, appropriated, and/or resisted by the individuals that they are directed toward. To address this gap, the current thesis identifies and maps out popular historical narratives that are shared by lay individuals embedded in the national context of the United States. Importantly, how and the extent to which these narratives are connected to the present-day context of nations is a key consideration throughout this endeavour. According to theories of collective remembering (Assmann, 2013; Rigney, 2005), historical narratives that are ‘active’ in public discourse ought to incorporate elements from the nation’s distant, mythologized past in continuity with their more recent, living memories to connect the past meaningfully to the present, and to inform a meaningful and coherent sense of national identity over time. By investigating the dynamics of historical narratives, representations, and identity at the level of individuals, while still incorporating the political and social contexts that they are embedded in, the current thesis contributes to bridging the gap between psychology and politics in the domain of collective remembering. Chapter 2 investigated how communicative memories (memories of public events that have occurred within the lifetimes of people alive or personally remembered today) index the present-day climates of societies. The findings from this chapter demonstrated how recent memories of terrorism drive an extreme negative climate in Western countries, while recent memories of national independence underpinned a positive climate across majority world countries. In Chapter 3, I explored how historical narratives are articulated by individuals (embedded in the American context) to give meaning to these historical representations, and thereby orient the nation’s past to its present. This chapter identified popular historical narratives which were anchored in positive representations of national foundations, and in turn, were positively associated with national identification. However, these were identified alongside a popular counter-narrative that was critical of the mythologization of America’s past. Moreover, there was considerable plurality and fragmentation in the narrative landscape, with many American participants failing to articulate a distinct historical narrative at all. In Chapter 4, I employed an experimental approach to show how this fragmentation is reduced, while endorsement of positive narratives about the nation becomes tighter when individuals are reminded of: 1) national foundations (the past reinforcing the present) and 2) a present-day context of intergroup threat (the present reinforcing the past). In Chapter 5, I discuss the theoretical and methodological implications of the studies and their findings within a dynamic framework of historical narrative and identity. The societal relevance of these findings is discussed in relation to the declining resonance of positive national narratives in the United States, amidst increasing domestic polarization and recent failures of the state to respond to crises. This has implications for the narrative resources that are available to political leaders in their rhetoric to mobilize the national identity of their followers and audience. Nonetheless, such rhetorical work does not occur within a vacuum, and the changing social/political context (see Chapter 4) may (re)activate the narratives that are still available within the minds of ordinary Americans today (see Chapter 3)
Keywords: Intergroup relations; New Zealand; History; Group identity; Political oratory; Maori (New Zealand people); Social classes; Politics and government; 19th century; Agent (Philosophy)